Long‐Lived Excited States of Zwitterionic Copper(I) Complexes for Photoinduced Cross‐Dehydrogenative Coupling Reactions. Issue 3 (20th November 2014) - Wang, Bin; Shelar, Deepak Prakash; Han, Xian‐Zhu; Li, Ting‐Ting; Guan, Xiangguo; Lu, Wei; Liu, Kun; Chen, Yong; Fu, Wen‐Fu; Che, Chi‐Ming
Abstract Four heteroleptic copper(I) complexes containing phenanthroline and monoanionic nido‐carborane‐diphosphine ligands have been prepared and structurally characterized by various spectroscopic techniques and X‐ray diffraction. These complexes exhibit intense absorptions in the visible range and excited‐state lifetimes on the microsecond scale. Their application in visible‐light‐induced cross‐dehydrogenative coupling reactions was investigated. Preliminary studies showed that one of the four copper(I) complexes is an efficient catalyst for photoinduced oxidative CH functionalization using oxygen as oxidant. Furthermore, α‐functionalized tertiary amines were obtained in good‐to‐excellent yields by light irradiation (λ>420 nm) of a mixture of our CuI complex, tertiary amines, and a variety of nucleophiles (nitroalkane, acetone, or indoles) under aerobic conditions. Electron paramagnetic resonance measurements provided evidence for the formation of superoxide radical anions (O2−⋅) rather than singlet oxygen (1O2) during these photocatalytic reactions.